Modernist Journals Project.
The Modernist Journals Project is a research and teaching resource on the rise of modernism in the English-speaking world, with a central focus on periodical literature. The Modernist Journals Project digitizes English-language literary magazines from the 1890s to the 1920s. We also offer essays and other supporting materials from the period.
Https://dada.lib.uiowa.edu
Database
Keywords: modernisme; tijdschriften